Estimated Dissemination Ratio—A Practical Alternative to the Reproduction Number for Infectious Diseases - Pérez-Reche, Francisco J.; Taylor, Nick; McGuigan, Chris; Conaglen, Philip; Forbes, Ken J.; Strachan, Norval J. C.; Honhold, Naomi (Frontiers in Public Health, 2021)
Policymakers require consistent and accessible tools to monitor the progress of an epidemic and the impact of control measures in real time. One such measure is the Estimated Dissemination Ratio (EDR), a straightforward, easily replicable, and robust measure of the trajectory of an outbreak that has been used for many years in the control of infectious disease in livestock. It is simple to calculate and explain. Its calculation and use are discussed below together with examples from the current COVID-19 outbreak in the UK. These applications illustrate that EDR can demonstrate changes in transmission rate before they may be clear from the epidemic curve. Thus, EDR can provide an early warning that an epidemic is resuming growth, allowing earlier intervention. A conceptual comparison between EDR and the commonly used reproduction number is also provided.